Pelvic floor dysfunction in women: current understanding of the problem - O. V. Remneva; I. S. Ivanyuk; A. I. Gal'chenko (Фундаментальная и клиническая медицина)
Here we review the recent literature on pelvic floor dysfunction, which is increasingly common in women of reproductive age and represents a significant medical problem occurring as a result of injured pelvic floor ligaments. Pelvic floor dysfunction is largely associated with vaginal delivery and might lead to urinary and fecal incontinence as well as pelvic organ prolapse. Intraabdominal hypertension, nerve damage, obesity, and genetic predisposition are among the major contributors to pelvic floor dysfunction. Being asymptomatic at the early stage, pelvic floor dysfunction gradually leads to the irreversible alterations in pelvic floor anatomy, ultimately deteriorating quality of life. Surgery remains a gold standard in the treatment of pelvic organ prolapse, yet POP-Q stage I-II prolapse should be treated conservatively. Currently, there are no specific treatment regimens and no evidence-based opinion regarding Kegel exercises and laser therapy. Biofeedback pelvic floor muscle training is the treatment of choice for urinary incontinence. Use of pessaries represents another efficient approach to conservative treatment.